The Influence of The Total of Production and Demand for Products on Income Level of Brick Residents in Klopo Sepuluh Gedangan Village – Sidoarjo Post Covid'19 Pandemic - Ike Susanti; Lilik Nur Cholidah (Institute of Computer Science (IOCS), 2021)
Brick business is a business that produces raw materials into ready-to-use goods that are used for building houses or high-rise buildings. By using cement and sand as the main raw materials. The purpose of this study is to determine the amount of production (X1) and product demand (X2) affect the level of income (Y) of the bricks of the residents of Klopo Ten Gedangan Village - Sidoarjo after the Covid-19 Pandemic. The data analysis method used is the quantitative method, the analysis used in this study is multiple correlation, coefficient of determination, multiple linear regression analysis, T-test and F_test, data processing using the SPSS statistical program. The conclusion of the research results show that the amount of production (X1) and product demand (X2), has a significant and positive effect on the level of income (Y). Product Demand is the most dominant variable. Judging from R2, which is 95 percent, it can be concluded that the diversification of product demand at 5 percent can be determined from other variables that are not included in the regression equation model in this study.